Quality of Outpatient Care Services at the City General Hospital of Tanjungpinang - Sumardiana Sumardiana*; Ayuning Budiati; Dwi Putranto Riau (Universitas Syiah Kuala, 2023)
Health services are the main priority of the organizers because it is one of the community's fundamental rights, and its provisions must b carried out by the government. In order to fulfill the need for health facilities, the government has made efforts to improve the quality of health facilities, including by making health care guarantees. This Regional General Hospital is located as a Regional Technical Institution that supports the implementation of the Regional Government. However, phenomena related to services at the Regional Government were found. The goal to b achieved is to find out and analyze how Big the Level of Outpatient Service Quality is at the Tanjungpinang City Regional General Hospital. In this study, the population was consumers or outpatients at Tanjungpinang Hospital in January -November 2022, namely 35,181 people. (2022), and a sample of 100 people. This study uses descriptive statistics, which use data to explain or draw conclusions about a group. Based on the study's results, the service quality at the Tanjungpinang City Hospital is of high quality, with a score of 3.1. But there is still something that needs to b improved, namely Reliability with a value of 2.98 and Tangibles with a value of 2.90, where it seems that there are still doctors who do not come on time so that makes the patient wait.